Radiative flow of Maxwell nanofluid containing gyrotactic microorganism and energy activation with convective Nield conditions. Issue 5 (21st March 2019) - Waqas, Hassan; Khan, Sami U.; Shehzad, Sabir A.; Imran, M.
Abstract: On the account of industrial and technological applications, the enhancement of energy by inserting nanoparticles is a hot topic in the present century. Therefore, the current analysis presents a theoretical analysis regarding the flow of electrically conducted Maxwell nanofluid over a stretching surface in the presence of the gyrotactic microorganism. In addition, the influence of thermal conductivity and Arrhenius activation energy are considered. By using the apposite transformation, the system of contemporary partial differential expressions is first converted into nonlinear ordinary differential system. The set of these transmuted equations is solved with the help of the shooting method. Reliable results are obtained for the velocity profile, temperature, motile microorganism density and concentration. It is evaluated that by increasing the value of bioconvection Peclet and Lewis numbers, the microorganism distribution exhibited diminishing behavior. These results may be useful in improving the efficiency of heat transfer devices and microbial fuel cells.